Influence of the infill geometry of 3D-printed tablets on drug dissolution - Venâncio, Nuno (2022)
Communication abstract: Proceedings of the 5th International Congress of CiiEM - Reducing inequalities in Health and Society, held at Egas Moniz’ University Campus in Monte de Caparica, Almada, from June 16th to 18th, 2021.